The making of European society: contesting methodological nationalism. Issue 1 (2nd January 2016) - Delanty, Gerard
Abstract : The paper is concerned with the problem of "society" and in particular with the notion of "European society". Rather than reject the possibility of society, it draws on theories of the social as networks. The thesis proposed is that the concept of society should rather be understood as a relational field of interconnections. It is argued that this is highly relevant to the analysis of Europe conceived of in terms of a society. This approach can be seen as an alternative to methodological nationalism. The paper applies a network conception of society to Europe with the emphasis on the nineteenth century. In this account, European society is not something that was produced by European integration. Rather than see European society as a recent development, it is argued that the field of tensions between capitalism and democracy constituted the major elements that shaped a European model of society.